Rationality Participation of Members of The Tulip Joint Business Group (KUBE) in Corn Planting in Pagarawan Village, Merawang District - Risti Rosmiati; Aimie Sulaiman; Herdiyanti (Social Science Studies, 2022)
The Joint Business Group (KUBE) aims to provide the community with access to potential and resources, hoping that it will be based on community empowerment, so that the process of improving the common good can be more effective and efficient. This study aims to analyze the justification for the participation of KUBE Tulip members in the cultivation of maize when there are obstacles, what causes these obstacles. This research was supplemented by a descriptive qualitative method using methods of data collection through interviews, observation and documentation. This study found that the most dominant action rationality behind KUBE Tulip member participation was instrumental rationality. However, his objective is influenced by affective rationality, which result in a lack of member participation in the implementation of the program. The lack of participation of members is based on the existence of disputes between groups, the diversification of work and the emergence of new habits and is repeated. This rationality is normalized by the members of the group during the execution of the program. Program Kelompok Usaha Bersama (KUBE) hadir untuk memberikan akses kepada masyarakat terhadap potensi dan sumber dengan harapan berbasis pemberdayaan masyarakat sehingga proses peningkatan kesejahteraan masyarakat dapat berjalan lebih efektif dan efesien. Penelitian ini bertujuan untuk menganalisis rasionalitas yang melatarbelakangi partisipasi anggota KUBE Tulip dalam penanaman jagung, apabila terdapat kendala maka hal apa yang menyebabkan kendala tersebut terjadi. Penelitian ini diselesaikan dengan metode kualitatif deskriptif dengan metode pengumpulan data melalui wawancara, observasi, dan dokumentasi. Penelitian ini menemukan bahwa rasionalitas tindakan yang paling dominan dalam melatarbelakangi partisipasi anggota KUBE Tulip adalah rasionalitas instrumental. Namun tujuan tersebut dipengaruhi oleh rasionalitas afektif sehingga menjadikan kurangnya partisipasi anggota dalam pelaksanaan program. Kurangnya partisipasi anggota kelompok dilandasi oleh adanya perselisihan antar kelompok, adanya diversifikasi pekerjaan, serta munculnya kebiasaan baru dan dilakukan secara berulang. Rasionalitas tersebut dinormalisasikan oleh anggota kelompok dalam menjalankan program.